2013
DOI: 10.4236/wjet.2013.12002
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modification of Sand Cast Eutectic Al-Si Alloys with Sulfur/Sodium and Its Effect on Mechanical Properties

Abstract: In the present study, the structural modification of sand cast Al-12wt%Si alloy with sulfur/sodium and its effect on mechanical properties were investigated. Different addition levels of sulfur and sodium were used to modify and produce castings of the same shape and size from the alloy. The results indicated that the addition of sodium or sulfur to eutectic Al-Si alloy can modify the Al-Si eutectic morphology from needle-like eutectic silicon structure to fine-scale eutectic silicon structure with significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
3
10
0
1
Order By: Relevance
“…6-9) machinability section support each other. The data obtained from the study are in compliance with literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Machining Propertiessupporting
confidence: 66%
See 3 more Smart Citations
“…6-9) machinability section support each other. The data obtained from the study are in compliance with literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Machining Propertiessupporting
confidence: 66%
“…Within this scope, among the significant aluminium alloys most commonly used in today's industries is Al-Si alloys [4,7,8,10]. It is observed that the studies conducted on aluminium alloys generally focus on such subjects as microstructure and mechanical properties analyses, hardness and creep properties analysis, porosity formation, ageing characteristics and surface roughness analyses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, aluminium alloys are commonly used in numerous industries, predominantly in automotive, transport, aviation, and aerospace industries [1][2][3][4][5][6][7][8]. In addition to aluminium alloys being plentiful in nature, their facility to produce, machine, and mould, being lightweight and their improvable mechanical properties also increase the place of use and importance of these alloys even more in today's industries [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%